2022
DOI: 10.1007/s40830-022-00396-9
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Finite Element Simulation of Shape Memory Bending Microactuator

Abstract: Due to their high-energy density, shape memory alloys (SMAs) are investigated as material for bending microactuators in applications of self-folding structures, realizing the concept of programmable matter. Here, for the numerical prediction of the electro-thermo-mechanical performance, the quantification of the time-dependent coupling effects in SMA materials during phase transformation is of crucial interest. Isothermal SMA material models cannot treat the time-dependent interaction between deformation, temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…As pointed out in [32, Assumption 2], if we choose the values of τ x and V L in a physically meaningful way, the transition probabilities p M A and p M A defined in ( 5) behave approximately as high-gain threshold functions. As a result, (4) becomes responsible for the high numerical stiffness of model (17). Following the analysis in [32], it can be shown that during phase transformation (i.e., ẋM ̸ = 0) the following approximation tightly holds for the polycrystalline model ( 17)…”
Section: B Characterization Of the Operative Modesmentioning
confidence: 99%
See 3 more Smart Citations
“…As pointed out in [32, Assumption 2], if we choose the values of τ x and V L in a physically meaningful way, the transition probabilities p M A and p M A defined in ( 5) behave approximately as high-gain threshold functions. As a result, (4) becomes responsible for the high numerical stiffness of model (17). Following the analysis in [32], it can be shown that during phase transformation (i.e., ẋM ̸ = 0) the following approximation tightly holds for the polycrystalline model ( 17)…”
Section: B Characterization Of the Operative Modesmentioning
confidence: 99%
“…The hybrid reformulation is grounded on the MAS model structural property defined by ( 19)- (20). Indeed, by using ( 19)- (20), we can compute x M without the need to integrate the stiff equation ( 4), therefore improving the numerical properties of model (17), as shown in the sequel. As a first step, a set of operative modes needs to be identified.…”
Section: B Characterization Of the Operative Modesmentioning
confidence: 99%
See 2 more Smart Citations